2013
DOI: 10.1080/15524256.2013.846889
|View full text |Cite
|
Sign up to set email alerts
|

Community Systems Strengthening for HIV Care: Experiences From Uganda

Abstract: The growing HIV burden on families and health systems is exerting a shift toward community caregivers, and is increasing the demand for functional community systems. In Uganda, where the number of people with HIV is increasing against a background of weak health systems, the role of community systems is poorly understood. We investigated the role of community systems in palliative care and the system elements required for an effective community response in Uganda. Qualitative interviews and focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…Programs including community awareness, voluntary counselling, testing campaigns and others have been initiated in Ethiopia [27,28], but are currently insufficiently performing. The current study participants, with one voice, mentioned a lack of consistent commitment to implementing these programs as part of reasons for the underperformance of these programs (see Box 1, Quote 1), as also supported by other studies [29,30]. Box 1.…”
Section: Theme 1: Strengthening Existing Programssupporting
confidence: 55%
“…Programs including community awareness, voluntary counselling, testing campaigns and others have been initiated in Ethiopia [27,28], but are currently insufficiently performing. The current study participants, with one voice, mentioned a lack of consistent commitment to implementing these programs as part of reasons for the underperformance of these programs (see Box 1, Quote 1), as also supported by other studies [29,30]. Box 1.…”
Section: Theme 1: Strengthening Existing Programssupporting
confidence: 55%
“…However, our line of argument is that among men, notions of masculinity do have an impact on their real or perceived ability to utilise services. This is particularly relevant given that in our study districts participation of men in HIV care was low [ 28 ]. In another study in Mbale district, Byamugisha et al [ 35 ] revealed that poor attendance by men in health clinics was attributed to them " being busy trying to make ends meet ", and a belief that men who accompany their wives to clinics are ‘ weaklings ’ (p.5).…”
Section: Discussionmentioning
confidence: 99%
“…Data published so far suggest that the project succeeded in mobilising communities of people living with HIV not only to access services but also to participate actively in HIV service delivery; for instance, by challenging stigma, counselling others, providing home-based and palliative care, and referring others to HIV services. However, ‘limited involvement of men’ in service uptake and provision was noted [ 28 ], p.352].…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review evaluating end-of-life care in Sub-Saharan Africa identified that of the 51 articles included, 38 (74.5%) dealt with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) [49]. One study showed the importance of the community in helping others who had experienced loss to HIV/AIDS [50]. However, the Gysels et al systematic review also identified three studies that showed how bereavement and grief were complicated after HIV/AIDS due to the social stigma and silence associated with that diagnosis [49].…”
Section: Infectious Diseasementioning
confidence: 99%